Cellular Crosstalk in the Vascular Wall Microenvironment: The Role of Exosomes in Vascular Calcification - Wu, Yun-Yun; Shan, Su-Kang; Lin, Xiao; Xu, Feng; Zhong, Jia-Yu; Wu, Feng; Duan, Jia-Yue; Guo, Bei; Li, Fu-Xing-Zi; Wang, Yi; Zheng, Ming-Hui; Xu, Qiu-Shuang; et al. (Frontiers in Cardiovascular Medicine, 2022)
Vascular calcification is prevalent in aging, diabetes, chronic kidney disease, cardiovascular disease, and certain genetic disorders. However, the pathogenesis of vascular calcification is not well-understood. It has been progressively recognized that vascular calcification depends on the bidirectional interactions between vascular cells and their microenvironment. Exosomes are an essential bridge to mediate crosstalk between cells and organisms, and thus they have attracted increased research attention in recent years. Accumulating evidence has indicated that exosomes play an important role in cardiovascular disease, especially in vascular calcification. In this review, we introduce vascular biology and focus on the crosstalk between the different vessel layers and how their interplay controls the process of vascular calcification.